Analysis Of The Judge's Ruling Regarding The Indonesian National Arbitration Board (BANI) (Decision Study Number: 305/Pdt.G/BANI/2014/PN Jkt.Utr) - Dyah A, Tata Eliestiana; Jamaludin, Jamaludin (Dinasti Research, 2025)
This research was conducted with the aim of finding out: 1) The basis for the judge's considerations in granting the applicant's request in decision number: 305/Pdt.G/BANI/2014/PN Jkt.Utr), 2) Analysis of the case resolution in decision number: 305/Pdt.G/BANI/2014/PN Jkt.Utr). The type of research used in this research is normative legal research using statutory, conceptual and case approaches. The results of this research show that: 1) The judge's basis for granting the Petitioner's petition in Decision Number: 305/Pdt.G/BANI/2014/PN Jkt.Utr was that the judge assumed that BANI Decision Number 513/IV/ARB-BANI/2013 was taken as a result of deception on the part of the Arbitration Petitioner. Then the Arbitration Panel made a real mistake in deciding the case regarding the use of the legal basis for decision making. Apart from that, the judge considers that BANI Decision Number 513/IV/ARB-BANI/2013 has violated the principle of freedom of contract and agreement law as regulated in Article 1338 of the Civil Code and Respondent II as the Decision Panel has given a decision that exceeds the demands in the Application for Arbitration. 2) Analysis of the case resolution regarding Decision Number: 305/Pdt.G/BANI/2014/PN Jkt.Utr), the Petitioner believes that Arbitration Decision No. 513/IV/ARB-BANI/2013 was taken from a ruse. However, the Petitioner did not explain in detail what form of deception was carried out by the Arbitration Panel, so this is a tendentious and far-fetched accusation. There was not a single trick carried out against the litigants. And if it is a trick, then it must be based on a court decision that has permanent legal force. This is based on the Decision of the Supreme Court of the Republic of Indonesia dated March 30 2009 No. 729K/PDT.SUS/2009.